2007
DOI: 10.1002/lt.21246
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of N-acetylcysteine in children with non-acetaminophen-induced acute liver failure

Abstract: Acute liver failure (ALF) carries a high mortality in children. N-acetylcysteine (NAC), an antioxidant agent that replenishes mitochondrial and cytosolic glutathione stores, has been used in the treatment of late acetaminophen-induced ALF and non-acetaminophen-induced ALF. In our unit, NAC was introduced as additional treatment for non-acetaminophen-induced ALF in 1995. The aim of this study was to evaluate the safety and efficacy of NAC in children with ALF not caused by acetaminophen poisoning. A retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
69
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 31 publications
3
69
1
3
Order By: Relevance
“…They recommended routine use of NAC in the dose of 100 mg/kg/day in all cases of ALF irrespective of the etiology. This was based on a retrospective single site review involving 170 children done by Kortsalioudaki, et al [2]. In this study NAC was associated with a shorter length of hospital stay, higher incidence of native liver recovery without transplantation, and better survival after transplantation.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…They recommended routine use of NAC in the dose of 100 mg/kg/day in all cases of ALF irrespective of the etiology. This was based on a retrospective single site review involving 170 children done by Kortsalioudaki, et al [2]. In this study NAC was associated with a shorter length of hospital stay, higher incidence of native liver recovery without transplantation, and better survival after transplantation.…”
mentioning
confidence: 97%
“…N-acetyl cysteine (NAC) replenishes mitochondrial and cytosolic glutathione stores and is the treatment of choice for acute acetaminophen toxicity. Studies in the past have shown some role of NAC in non-acetaminophen ALF [2,3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Liver Transplantation, Kortsalioudaki et al 7 describe the presentation, management, and outcome of a large series of patients diagnosed with non-APAP-induced ALF who have been treated with NAC. Several prior studies have reported the use of NAC for non-APAP-induced ALF; however, the number of patients reported has been low and none of the studies have been adequately controlled.…”
mentioning
confidence: 99%
“…In the current study, Kortsalioudaki et al 7 performed a retrospective analysis of 170 children diagnosed with non-APAP-induced ALF at King's College Hospital between 1989 and 2004. A total of 59 patients (Group 1) treated from 1989 to 1994, an era prior to the routine use of NAC for non-APAP-induced ALF at this institution, were compared to 111 children (Group 2) diagnosed between 1995 and 2004.…”
mentioning
confidence: 99%